Peran Media Baru dalam Meningkatkan Partisipasi Politik Generasi Z (Studi: Penggunaan TikTok sebagai Sarana Pemasaran Politik Partai Kebangkitan Bangsa Menuju Pemilu 2024) - Rois, Alamudin Dimyanti (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
New media, such as TikTok, serves as an interactive digital platform that enables users to directly participate in accessing and disseminating information. This study is motivated by a gap in understanding the effectiveness of social media as a political marketing tool for Generation Z, particularly within the Indonesian political context, which requires tailored content to engage this young voter demographic. Using a qualitative method with in-depth interviews, this research involved 100 respondents from Generation Z who are active TikTok users, as well as officials from the National Awakening Party (PKB) at both central and regional levels. The study aims to analyze the types of TikTok content most effective in enhancing Gen Z’s political participation leading up to the 2024 election. The results show that content with entertaining, informative, and narrative-based styles strongly appeals to Gen Z, proving effective in fostering their political engagement. The study concludes that PKB's strategy of using TikTok, through an interactive and Gen Z-preferred content approach, effectively increases political participation and could serve as an innovative model for future political campaigns.